SPE Annual Technical Conference and Exhibition 2013
DOI: 10.2118/166343-ms
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Polymer/LPS Injectivity Test with Focus on Operational Feasibility and Near Wellbore Response in a Heidrun Injector

Abstract: Increased oil recovery technologies are very important for the large Heidrun field located in the Norwegian Sea. Very harsh climate and stringent environmental regulations render enhanced oil recovery (EOR) projects challenging. One EOR method evaluated for the field is polymer/LPS (Linked Polymer Solution) with the objective to improve the reservoir sweep. An offshore polymer and LPS injectivity test was performed with the objectives to determine the logistical and operational feasibility of handling polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Recent review work summarizes the available polymers for use in high temperature and high salinity reservoirs [10,11]. These polymers are mainly based on acrylamide.…”
Section: Types Of Polymers For Eor Applicationsmentioning
confidence: 99%
“…Recent review work summarizes the available polymers for use in high temperature and high salinity reservoirs [10,11]. These polymers are mainly based on acrylamide.…”
Section: Types Of Polymers For Eor Applicationsmentioning
confidence: 99%
“…Selle et al [22] discuss the development of a polymer injection project on the Heirun platform in the North Sea. They review previously reported application of polymer flood offshore and point out that there were three projects reported in the period prior to 1990 which represents the initial phase of interest in offshore polymer flood.…”
Section: Produced Water Handling For Eor Back Produced Fluidsmentioning
confidence: 99%
“…LPS has been implemented successfully at onshore fields in China , and extensive core flood experiments have showed high recovery potential. ,, However, only one injection pilot has been performed at offshore field . To adapt LPS to offshore conditions, the properties have to be optimized to meet specific requirements regarding pH, salinity and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…7,9,10 However, only one injection pilot has been performed at offshore field. 45 To adapt LPS to offshore conditions, the properties have to be optimized to meet specific requirements regarding pH, salinity and temperature. Physicochemical properties have been studied by rheology and dynamic light scattering (DLS).…”
Section: ■ Introductionmentioning
confidence: 99%